The Effect of Special Exercises in the Development of Some Sense of Mobility and its Contribution to the Skillful Performance of Futsal Players - Ali Falah Mohamed Hassan (Journal of Global Pharma Technology, 2019)
The game of football is one of the most popular games in the world and this game enjoys great care and attention everywhere, because it is one of the most popular games in the countries of the world and the characteristics and variables of search of perceptions of sense - motor and the proportion of its contribution to the performance of the skills of football halls. The aim of the letter is to: Prepare exercises in the development of some sense of mobility for football players of the halls. The study hypotheses were: There were significant differences in the results of the Pre and Post measurements and for the two groups of research (control, experimental) and for the sake of distance measurements. There were significant differences in the results of the dimension measurements and the two groups of research (control, experimental) and for the benefit of the experimental group. The problem of research in some of the club exercises was observed. There is a lack of attention to the dimensions that directly affect the performance of the skills, including the cognitive requirements, despite their importance. So the researchers wanted to go into the study of this problem a pilot study was the development of special exercises to develop awareness (sense - motor) and then the extent of his contribution to the development of the skillful performance of the players of football halls. The research community consists of players of the fans club for the sports season (2017-2018) and one of the clubs was chosen by lottery (18 players). The most important sensory movements that contribute to the skillful performance of the Futsal Hall were identified through a questionnaire distributed to specialists and obtained special perceptions (Time and place and ball) the highest ratios and then the tests were chosen for the research and modified one of them to suit the subject and after the homogeneity and the experiment was carried out for two times and then conducted Pretests on the members of the research sample and then was given special exercises for the experimental group and adopted the group الظا The course was conducted on the trainer's curriculum and lasted for two months and varied methods of giving exercises to fit the best performance and taking into account the training bases and after the tests were carried out in the same conditions as in the Pretests, the fourth section included the presentation of the results and analyzed and discussed by the researchers put them in the tables and which are illustrative means of what came Results of the study in order to identify the validity and conformity of the objectives of the study and its mandate to analyze the reality of the differences between the Pre and Post tests of the two groups as well as the contribution ratios of perceptions sense of movement and skill performance of the post-test MJ Experimental anguish In order to achieve the objectives of the study researcher used the bag statistical (SPSS) .Thus to reached several conclusions and recommendations of the most important of which there is a positive influence in the development of dynamic perceptions _football players lounges and two sets of research (experimental, control), but to varying degrees. The experimental group, which adopted the exercise exercises, showed a clear superiority over the control group in all the post-tests. Based on these results, the researchers recommended the following: The recommended exercises should be used to develop the level of awareness of the players of the football player’s .And the need for the attention of coaches’ players, including the category of applicants to develop the level of perceptions sense - kinetic to meet the requirements of the skills, planning …Football.Keywords: Special exercises, Mobility, Contribution, Skillful performance and futsal.